Clients’ experiences of psychodynamic therapies:: A phenomenological study - Fellows, Jodie Louise; Watters, Camilla; Gatherer, Amanda (European Journal for Qualitative Research in Psychotherapy, 2012)
This study aimed to explore clients’ experiences of psychodynamic therapies. Six adults were interviewed about their experiences of psychodynamic/brief psychodynamic therapy at varying stages of the process. Interpretative Phenomenological Analysis with peer review was used to analyse the transcripts. The therapeutic relationship was central to the experience of therapy, and a number of other factors were highlighted as contributing to the experience. Participants also described their journeys through therapy; from initial anxiety to developing trust, exploring difficulties and developing understanding of these. The process of making change in line with the new understanding was experienced as difficult and frustrating, but ultimately worthwhile. Ending therapy for all participants was associated with intense feelings such as, terror, anger and abandonment. This was followed by a development of self-reliance once therapy had terminated. The potential clinical benefits of detailed knowledge of clients’ experiences are discussed and potential future research options are considered.